Two cases of childhood linear immunoglobulin A bullous dermatosis following multivisceral transplant: A case report - Adam C Yu; Airiss R Chan; Kerry Wong; Kirsten Walker; Loretta Fiorillo (SAGE Open Medical Case Reports)
Childhood linear immunoglobulin A bullous dermatosis is a well-recognized autoimmune blistering dermatosis that can be idiopathic, drug-induced, secondary to autoimmune diseases, malignancies, infections, or gastrointestinal diseases including inflammatory bowel disease. However, it has not been previously associated with a history of organ transplantation. Here, we report two cases of childhood linear immunoglobulin A bullous dermatosis in young infants following multivisceral organ transplant, including one with a particularly recalcitrant course. We propose potential mechanisms contributing to the development of linear immunoglobulin A bullous dermatosis and challenges in the management of these patients in light of their complex medical histories and immunosuppression.